2021
DOI: 10.1386/ijis_00043_1
|View full text |Cite
|
Sign up to set email alerts
|

Everyday life under the PIDE: A quantitative survey on the relations between ordinary citizens and Salazar’s political police (1955–74)

Abstract: This article examines the relations between Portuguese society and Salazar’s political police (PIDE) from the perspective of the everyday lives of ordinary citizens – in contrast to the small minority of oppositionists that has so far monopolized the attention of historians. It is based on a quantitative survey of 400 respondents in four separate locations across Portugal and addresses two main research questions: To what extent did the sample of ordinary citizens experience the PIDE as a disruptive influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
0
0
Order By: Relevance
“…Regarding mainland Portugal, Duncan Simpson has recently shown that the relation between society and PIDE/DGS was more complex and interactive than the traditional narrative of top-down violence and repression has it. 106 In my view, research on the war in Mozambique would also benefit from a more open-ended analysis of the complex relations between PIDE/DGS, the military, and society.…”
Section: Assumption I: Archival Documents Do Not Contain Information ...mentioning
confidence: 99%
“…Regarding mainland Portugal, Duncan Simpson has recently shown that the relation between society and PIDE/DGS was more complex and interactive than the traditional narrative of top-down violence and repression has it. 106 In my view, research on the war in Mozambique would also benefit from a more open-ended analysis of the complex relations between PIDE/DGS, the military, and society.…”
Section: Assumption I: Archival Documents Do Not Contain Information ...mentioning
confidence: 99%